(untitled) (SMC Journal Shadananda Multiple Campus, 2025)
This research explores the perceptions of Tamang community students in Shadananda Municipality, Bhojpur district, toward their mother tongue and the English language. The study aimed to answer the following research questions: Why is the perception towards their mother tongue decreasing? Why is the perception towards English increasing? And what strategies can develop a positive perception of their mother tongue while promoting English learning? The objectives of this research were to explore the perceptions of both languages among the students and to emphasize the importance of preserving the mother tongue while developing English communication skills. Employing an exploratory qualitative research design, the study utilized focus group discussions with twelve students from grades 10 and 12 and interviews with two secondary level teachers from community schools. The findings indicate a declining interest in the Tamang mother tongue due to the perceived lack of opportunities for its use and its perceived limited value for future prospects. Conversely, students show an increasingly positive perception of the English language, recognizing its importance for securing jobs, pursuing further education, facilitating communication, and accessing technology and global media. The research also identifies challenges in developing English communication skills, including the influence of the mother tongue’s phonetic patterns and the prevalent use of translation methods in teaching. The study suggests strategies for revitalizing the mother tongue, such as raising awareness of its significance, creating supportive environments for its use in various settings, and integrating it into school activities.